2007
DOI: 10.2138/rmg.2007.65.12
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Immiscibility in Metamorphic Rocks

Abstract: INTRODUCTIONEvidence of fluid immiscibility in metamorphic rocks comes, in the best of all worlds, from fluid inclusion observations. In fact, fluid immiscibility should be anticipated over the full range of metamorphic conditions provided that appropriate bulk fluid compositions are present. In a review paper on "Metamorphic fluids: the evidence from fluid inclusions" Crawford and Hollister (1986) summarized: "The role of fluid immiscibility in metamorphism was only recognized after serious study of fluid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 154 publications
0
42
0
Order By: Relevance
“…The occurrence of C-H-O fluid immiscibility in subduction zones is supported by the studies of fluids and fluid inclusions in high-pressure metamorphic rocks from subduction zones (Heinrich, 2007;Frezzotti and Ferrando, 2015). For example, Andersen et al (1993) reported coexistence of CO 2 -N 2 fluid inclusions and H 2 O-rich fluid inclusions with about 30 wt.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The occurrence of C-H-O fluid immiscibility in subduction zones is supported by the studies of fluids and fluid inclusions in high-pressure metamorphic rocks from subduction zones (Heinrich, 2007;Frezzotti and Ferrando, 2015). For example, Andersen et al (1993) reported coexistence of CO 2 -N 2 fluid inclusions and H 2 O-rich fluid inclusions with about 30 wt.…”
Section: Discussionmentioning
confidence: 86%
“…Firstly, C-H-O fluid immiscibility may cause extensive decarbonation in subduction zones. Previous studies show that some low-grade metamorphic reactions may cause extensive decarbonation if these reactions take place at H 2 O-CO 2 immiscibility (Yardley and Bottrell, 1988;Heinrich, 2007). Similarly, for a given decarbonation reaction in subduction zones, if it takes places at H 2 O-CO 2 immiscibility, significant amounts of carbonates may also be consumed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The third consequence of H 2 O-CO 2 and H 2 O-NaCl activity relations is an extensive region of immiscibility in H 2 O-CO 2 -salt ternaries at lower crustal conditions (e.g., Heinrich, 2007;Liebscher, 2010;Manning et al, 2013). Most work has been conducted at low pressure (Gehrig et al, 1979;Aranovich et al, 2010;Anovitz et al, 2004), but extension of these results to lower crustal conditions (Frantz et al, 1992;Johnson, 1991;Kotelnikov and Kotelnikova, 1990;Graham, 1999, 2004;Joyce and Holloway, 1993;Gibert et al, 1998) yields a ternary miscibility gap between NaCl-H 2 O-rich brine and CO 2 -H 2 O-rich vapor.…”
Section: Activity-composition Relations and Petrologic Consequences Omentioning
confidence: 99%